THE PSYCHOLOGICAL PECULIARITIES OF PUPILS’ ADAPTATION / DISADAPTATION AT PREPARATION FOR EXTERNAL INDEPENDENT TESTING UNDER THE QUARANTINE - Shtompel, Lubov (PSYCHOLOGICAL JOURNAL, 2020)
The article analyzes the psychological characteristics of pupils’ adaptation/ disadaptation during their preparation for external independent testing (EIT) under the Covid-19 quarantine. The pupils’ feelings, such as anxiety, inner turmoil and stresses, caused by internal and external disadaptive factors are determined. Adaptation was defined as a state and a process, which include many components: personality development (in particular, the performed study focuses on high school students, especially graduates under 17 years); rapid accelerated changes in the social environment, which requires an appropriate individual mobility; and a result of adaptation. The reviewed psychological literature distinguishes the following components of adaptation as a process: physiological changes; mental development; cognitive processes; transformation of values; active influence on a situation, including awareness of the situation, setting tasks, purposeful activities. Thus, adaptation as a process discloses an individual’s active potential, since it necessarily requires their active and purposeful attitude to the reality. The variants of adaptive behavior are analyzed from the points of views of different approaches. The approaches are differentiated in the base of different accents emphasized by researchers, in particular: the degree of activities; the direction of an individual’s or a group’s activities and so on. The proposed study is important because the global challenges that humanity is experiencing and for which no one is ready. We have found ways to get out of maladaptive conditions: distance learning, TV-lessons, task control, etc. All these aspects can help temper psychologically a young personality by forming such qualities as: self-education, self-control, a sense of responsibility towards oneself and the social environment.